Risk management in Lithuanian organizations – relation with internal audit and financial statements quality - Tamošiūnienė, Rima; Savčuk, Olga (Business: Theory and Practice, 2007)
Over the last few years the importance to the strong corporate governance of managing risk has been increasingly acknowledged. There is more opportunity and risk in today’s complex, dynamic and fast changing environment The new reality is that risks are swift, sudden and relentless; the sources of risks being less predictable, which not only adds to the challenge of managing, but forces businesses to review their approach to risk management and control. Organizations are under pressure to identify all the business risks they face: social, ethical and environmental as well as financial and operational, and to explain how they manage them to an acceptable level. Organizations operate in the environments where factors such as globalization, technology, regulation, restructurings, changing markets, and competition create uncertainty. Uncertainty is caused by an inability to precisely determine the likelihood that potential events will occur and their associated outcomes. Risk usually can be understood as an uncertainty about the events and their outcomes that could have material effect on the goals and objectives of the organization. Risk is the threat that the organization will not reach its objectives both facing the negative circumstances and also failing to utilize the opportunities, i.e. risk is a set of circumstances that hinder the achievement of the determined objectives. Therefore in order to reach its objectives each organization has to develop and implement an approach to assessing and managing the uncertainties and opportunities it faces in the pursuit of its business strategy, with the intention of maximizing shareholder value and performance, i.e. meeting the determined objectives. The underlying meaning of the risk management is that every organization, whether for-profit, not-for-profit, or a governmental body, exists to provide value for its stakeholders. All organizations face uncertainty, and the challenge for management is to determine how much uncertainty the organization is prepared to accept as it seeks to grow stakeholder value. Risk management of the organization provides a framework for management to effectively deal with the uncertainty and associated risk and opportunity and thereby enhance its capacity to build value. Any change in stakeholder value sooner or later must be reflected in the financial statements of the company. Only quality financial statements presenting true and fair view of the company’s activities can be used by stakeholders in decision making process. Effective risk management process ensures both increasing stakeholders value and quality of the financial statements, together supporting stakeholders trust. In case quality of financial reports is poor, companies might loose financial sources, trust of the investors, public, customers and suppliers. In current environment top and senior management of the organization more and more rely on the internal audit to evaluate whether controls are sufficient to manage risks and uncertainties. That is a tremendous responsibility, and over the years, leading internal audit functions have strived to meet this challenge. This developing role of the internal auditing is also reflected in its current definition, i.e. internal auditing is “an independent, objective assurance and consulting activity designed to add value and improve an organization’s operations. It helps an organization accomplish its objectives by bringing a systematic, disciplined approach to evaluate and improve the effectiveness of risk management, control and governance processes”. Efficient internal audit assisting the company in improving risk management and governance systems takes an active role in assuring high quality financial statements. Therefore internal audit is an important value added function each company should use to gain competitive advantage. These developments are very important for Lithuanian companies due to growing economy, increase in foreign investments and stronger pressure from business environment to improve risk management and governance systems. The purpose of this article is to research efficiency of the risk management systems in Lithuanian companies from the perspective of the quality of the financial statements and also to research whether the existence of the internal audit function impacts the risk management system efficiency through the quality of the financial statements, i.e. researching whether internal audit is effective in Lithuanian companies.